2015
DOI: 10.3928/1081597x-20150922-01
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Visual Quality of Intraoperative Orientation of Asymmetric Intraocular Lenses

Abstract: The results suggest that implantation of this nonrotational symmetric IOL should improve visual outcomes if it is oriented to coincide with a customized meridian. A simple, practical method is proposed to find an approximation to the angle that an Mplus IOL should be inserted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In a previous study we simulated pure simultaneous vision [11], an ideal situation in which the entire pupil is used for far vision and near vision at the same time, as it occurs in diffractive designs. On the other hand, computational studies have shown that the specific pupillary distribution for near and far produces differences in the thru-focus optical performance both in diffraction-limited eyes with multizone radial and angular distributions [14,24]), and in real eyes with angular bifocal patterns at different orientations [16,25]. The new simultaneous vision simulator presented in this study is capable of simulating any bifocal pupillary pattern, optically programmed by means of a Spatial Light Modulator, expanding the capability of simulating any refractive bifocal design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we simulated pure simultaneous vision [11], an ideal situation in which the entire pupil is used for far vision and near vision at the same time, as it occurs in diffractive designs. On the other hand, computational studies have shown that the specific pupillary distribution for near and far produces differences in the thru-focus optical performance both in diffraction-limited eyes with multizone radial and angular distributions [14,24]), and in real eyes with angular bifocal patterns at different orientations [16,25]. The new simultaneous vision simulator presented in this study is capable of simulating any bifocal pupillary pattern, optically programmed by means of a Spatial Light Modulator, expanding the capability of simulating any refractive bifocal design.…”
Section: Discussionmentioning
confidence: 99%
“…The patterns tested in this study include designs reminiscent of lenses existing in the market (i.e. bisegmented angular patterns such as that found in the M-Plus IOL, Oculentis Inc [15,16] tested in different orientations, or concentric bifocal patterns such as those found in the ReZoom, AMO [17]). A psychophysical paradigm was implemented to answer the following questions: Do some bifocal patterns provide better perceived quality than others?…”
Section: Introductionmentioning
confidence: 99%
“…We also included the neural contrast threshold (NCT) in the calculations. 23 This curve provides information on the minimum contrast that certain frequencies must have to be detected by the visual system. The intersection point between this curve and the real (OTF) allows for the determination of the cutoff frequency of the visual system.…”
Section: Numerical Evaluationmentioning
confidence: 99%
“…Схожие данные были получены в исследовании S. Bonaque-Gonzalez с соавт. [16], в котором на примере Lentis Mplus LS 312 MF был сделан вывод, что острота зрения не имеет статистических различий в случае имплантации ИОЛ в правильный или неправильный меридиан. Однако было установлено, что оптимальная ориентация интраокулярной линзы вызывает улучшение расчетного параметра качества изображения VSMTF (Visually modulated transfer function) на 58±19% по сравнению с неправильной ориентацией ИОЛ.…”
Section: A б влияние положения добавочного сегмента на остроту зренияunclassified